ANALISIS KARAKTERISTIK DAN TINGKAT PELAYANAN FASILITAS PEJALAN KAKI DI KAWASAN TERMINAL KENDARAAN UMUM KOTA DEPOK - Fajar Tri Utomo; A.R Indra Tjahjani (Jurnal Infrastruktur, 2017)
The study area was conducted in one of the Public Vehicle Terminals located in Depok (Margonda). The area of Public Vehicle Terminal located in Depok city is not only the center of the area where the temporary stops of public transportation to raise and lower the passengers, there is also a shopping center which causes pedestrian lane always crowded by pedestrians. Therefore, the research aimed to increase the knowledge and understanding about the comfort of a pedestrian path infrastructure, as well as to know the variable values of pedestrian characteristics, the relation of speed variables with the density, and the level of service of the pedestrian facility. Thus can be known the development function of the pedestrian facility. And the method used in the research refers to Regulation of Minister o f Public Work No. 03/PRT/M/2014. The data obtained from the observation are: the number of pedestrians, pedestrian travel time, and visual observation in the field. Data is processed into pedestrian characteristic variables such as: current, speed, density , and space. To obtain the relationship between speed variables and density variables according to Greenberg method, as well as the value form of capacity and service level of pedestrian facilities in Depok City Public Vehicle Terminal Area. And the improvement of pedestrian facilities can be maintained in the Depok City Public Vehicle Terminal Area. In accordance with the guidelines referring to the Regulation of the Minister of Public Works No. 03/PRT/M/2014.